Preparation of Cu2O Hollow Nanospheres Assisted by Tween-60 by a Simple Liquid Method - Xu, Juncui; Yao, Chenli; Wei, Yanxin (Asian Journal of Chemistry, 2010)
In this paper, cuprous oxide (Cu2O) hollow nanospheres have been synthesized by reducing copper sulphate with ascorbic acid in the presence of Tween-60 at room temperature. The method is simple and productive. The sample is characterized by X-ray powder diffraction, fieldemission scanning electron microscopy, transmission electron microscopy and ultraviolet-vis light (UV-vis) absorption spectra. A possible formation mechanism of Cu2O hollow nanospheres is discussed.